2014
DOI: 10.2203/dose-response.14-023.alleman
|View full text |Cite
|
Sign up to set email alerts
|

Why Does Exercise "Trigger" Adaptive Protective Responses in the Heart?

Abstract: Numerous epidemiological studies suggest that individuals who exercise have decreased cardiac morbidity and mortality. Pre-clinical studies in animal models also find clear cardioprotective phenotypes in animals that exercise, specifically characterized by lower myocardial infarction and arrhythmia. Despite the clear benefits, the underlying cellular and molecular mechanisms that are responsible for exercise preconditioning are not fully understood. In particular, the adaptive signaling events that occur durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 107 publications
1
15
0
1
Order By: Relevance
“…One way to achieve this would be augmenting angiogenesis. Exercise improves cardiac function [55], and increases angiogenesis and oxygen uptake efficiency [56]. Exercise therapy now has cautious recommendation in PAH guidelines [9].…”
Section: Discussionmentioning
confidence: 99%
“…One way to achieve this would be augmenting angiogenesis. Exercise improves cardiac function [55], and increases angiogenesis and oxygen uptake efficiency [56]. Exercise therapy now has cautious recommendation in PAH guidelines [9].…”
Section: Discussionmentioning
confidence: 99%
“…The main findings in the present study were that the expression levels of the examined molecules were dissimilar according to the neocapillarization extent and physical exercise intensity. Human epidemiological and animal studies have shown that a moderate to high intensity exercise is the best quantity that results in a reduction in the cardiovascular risk (Alleman et al., 2015). A recent paper reported that high intensity treadmill exercise training for up to 4 weeks produced greater increases in new capillary formation than low intensity exercise training in rat hearts (Waring et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Toks EKG rodiklių dinaminės sąsajos vertinimas (diskriminanto kaitos vertinimas) leidžia tiksliau palyginti pratybų liekamuosius efektus. Fiziniai krūviai aktyvina ilgalaikės adaptacijos mechanizmus, įvairios kūno sistemos ir jų funkcija kinta (Alleman, 2015). Kaip buvo atskleista daugelyje mokslo studijų (Venskaitytė, Poderys, Balagué, Bikulčienė, 2009;Poderys et al, 2010;Papievienė, 2014), fizinio krūvio pradžioje Dsk mažėja (sąsaja stiprėja), o krūviui sunkėjant ir atsirandant nuovargiui, sąsaja tarp daugelio EKG rodiklių pradeda silpnėti (Dsk reikšmės didėja).…”
Section: Aptarimasunclassified